GERTAKK & PUPUK CERIA: STRATEGI PENINGKATAN KETAHANAN PANGAN RUMAH TANGGA DI DESA PAGAR GUNUNG - Sindy Annisa Zahra; Victoria Safina Sugianto; Fadillah Arika; Salsabilla Putri; Karyn Agness Angellica Sagala; Yola Avanda; Nessa Widya Marbun; Miranda; Heni Rahmawati; M. Hersyah Rohmatullah; Widya Syaputri; Marini Aulia Syifa (PARIPALAKA SRIWIJAYA, 2025)
Food security is an important pillar of sustainable development in Indonesia, covering food availability, access, utilization and stability. Muara Enim Regency, including Pagar Gunung Village, still faces challenges in food diversification, high stunting, and limited access to clean water. To answer these challenges, the PBL student team of FKM Sriwijaya University implemented a family empowerment program through two main activities, namely GERTAKK (Family Consumption Food Planting Movement) and CERIA Fertilizer (Environmentally Friendly Liquid from Rice Water and Onion Peels). This program aims to improve household food security by utilizing narrow yards through the BUDIKDAMBER (Fish Farming in Buckets) method and processing household waste into liquid organic fertilizer. The activity was carried out on June 11, 2025 in the yard of the Pagar Gunung Village Head's house with an educational and participatory approach, involving 20 residents from six hamlets. The results of the activity showed an increase in knowledge, enthusiasm, and willingness of residents to utilize yard land and household organic waste independently. This simple and contextual strategy is effective in strengthening family food security in supporting a sustainable local food system.